Identifying Supply Chain Risks Influencing Contractor Profitability Using Structural Equation Modeling - Ananda, Fikri Arief; Putra, I Nyoman Dita Pahang (Civil and Sustainable Urban Engineering, 2026)
The construction supply chain involved complex interactions among stakeholders and was exposed to various risks that could affect contractor profitability. However, existing studies had rarely integrated Structural Equation Modeling (SEM) and the Relative Importance Index (RII) to simultaneously capture both statistical relationships and practitioners’ perceptions, particularly in the context of high-rise building projects in Indonesia. This study aimed to identify and analyze supply chain risks in the flows of information, materials, and funds and to examine their influence on contractor profitability. Data were obtained from structured questionnaires distributed to 50 respondents across five high-rise projects in Surabaya. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) alongside RII. The SEM results revealed that all three flows, information, materials, and finances, significantly improved contractor profitability, with information flow having the strongest effect. The RII rankings indicated that information risks were the primary concern, particularly unclear communication and errors in conveying project scopes. Comparing the statistical significance identified by SEM with the practical perceptions captured by RII revealed key gaps between measured impacts and practitioners’ views, thereby improving risk prioritization. Overall, this study advanced construction supply chain risk research by integrating SEM and RII methods, while providing practitioners with actionable recommendations to improve information sharing, streamline material handling, and strengthen financial management to enhance profitability.